Knowledge and interaction through diverse lenses - Markova, Ivana (2010)
The concepts like knowledge and interaction have acquired many different meanings in human and social sciences and consequently, the knowledge construction in cognitive science, computing, socio-biology and dialogicality refers to diverse processes. This article draws attention to such diversities in meanings of knowledge and interaction and to their ontologies. It first discusses the Cartesian, connectivist and neuro-biological approaches to knowledge and processing of information. It then presents a dialogical theory of knowledge based on the Ego-Alter interaction. It argues that knowledge is co-constructed jointly by the Ego-Alter, leading to the epistemological triadic relation the Ego-Alter-Object. Dialogical theory brings communication into the centre of the theory of knowledge. The last part of the paper discusses the construction of knowledge in and through communication genres, giving as examples persuasion and argumentation. - Conceitos como conhecimento e interacção têm assumido muitos sentidos diferentes nas ciências humanas e sociais e, consequentemente, a construção do conhecimento em ciência cognitiva, computação, sócio-biologia e dialogicalidade refere-se a diversos processos. Este artigo chama a atenção para estas diversidades nos sentidos do conhecimento e da interacção e para as suas ontologias. Começa por discutir as abordagens do conhecimento e processamento de informação Cartesianas, associacionistas e neuro-biológicas. Apresenta, em seguida, a teoria dialógica do conhecimento, baseada na interacção Ego-Alter. Assume que o conhecimento é co-construído conjuntamente pelo Ego-Alter, levando à relação triádica epistemológica Ego-Alter-Objecto. A teoria dialógica traz a comunicação para o centro da teoria do conhecimento. A última parte deste artigo discute a construção do conhecimento em e através dos estilos de comunicação, dando como exemplos a persuasão e a argumentação.